Composition for optical materials

KR103019593B1Active Publication Date: 2026-09-16MITSUBISHI GAS CHEM CO INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227036655
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-27
Filing Date
2021-05-21
Publication Date
2026-09-16
Estimated Expiration
2041-05-21

Smart Images

  • Figure 112022110822406-PCT00001
    Figure 112022110822406-PCT00001
  • Figure 112022110822406-PCT00002
    Figure 112022110822406-PCT00002
  • Figure 112022110822406-PCT00003
    Figure 112022110822406-PCT00003
Patent Text Reader

Abstract

According to the present invention, a composition for an optical material containing (a) an episulfide compound, (b) a polymerization catalyst, and (c) an ester compound having a halogen at the α-position can be provided. Preferably, the ester compound having a halogen at the α-position (c) is one or more compounds selected from the group consisting of dimethyl chloromalonicate, diethyl chloromalonicate, dimethyl bromomalonicate, and diethyl bromomalonicate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to compositions for optical materials, etc., and in particular, to optical materials such as plastic lenses, prisms, optical fibers, information recording bases, and filters, and among these, compositions for optical materials suitable for plastic lenses. Background Technology

[0002] Plastic materials are lightweight, have high toughness, and are easy to dye, so they are widely used in various optical materials, especially in eyeglass lenses. The performance characteristics particularly required for optical materials, and among them eyeglass lenses, include low specific gravity, high transparency and low yellowness, high heat resistance, and high strength as physical properties, and high refractive index and high Abbe number as optical performance characteristics. A high refractive index enables thinning of the lens, and a high Abbe number reduces chromatic aberration of the lens; however, since the Abbe number decreases as the refractive index increases, research is being conducted to improve both simultaneously. Among these research, the most representative method is the method using an episulfide compound as described in Patent Document 1.

[0003] Furthermore, to improve oxidation resistance, Patent Document 2 proposes a composition in which a thiol compound is added to an episulfide compound.

[0004] In addition, studies aimed at high refractive index are also being conducted, and compositions consisting of sulfur, episulfide, and thiol as shown in Patent Documents 3 and 4, and compositions consisting of a compound having a cyclic framework and episulfide as shown in Patent Document 5 have been proposed.

[0005] As such, episulfide compounds can be polymerized alone or with many other compounds due to their high reactivity, and it is possible to combine compositions according to various applications.

[0006] However, these episulfide compounds or compositions containing them have difficulties with workability because the viscosity increases when combined. In response to this, a method of adding halides of elements in groups 13 to 16 of the long-period periodic table shown in Patent Document 6 has been proposed.

[0007] However, even when these methods were employed, there were cases where the resin coloring, the color change after heating, or the color change after light irradiation deteriorated, making it difficult to maintain a good balance of these physical properties. Therefore, a method was desired that could suppress the increase in viscosity during mixing while also maintaining a good balance of the resin coloring after curing, the color change after heating, and the color change after light irradiation. Prior art literature

[0008] Japanese Patent Publication No. H9-110979 Japanese Patent Publication No. H10-298287 Japanese Patent Publication No. 2001-2783 Japanese Patent Publication No. 2004-137481 Japanese Patent Publication No. 2010-242093 Japanese Patent Publication No. 2002-332350 The problem to be solved

[0009] The problem that the present invention aims to solve is to provide a composition for optical materials that suppresses an increase in viscosity during mixing and also maintains a good balance of the coloration of the resin after curing, the color change after heating the resin, and the color change after light irradiation of the resin. means of solving the problem

[0010] The inventors, taking these circumstances into account and through repeated research, have solved the problem by a composition for optical materials containing (a) an episulfide compound, (b) a polymerization catalyst, and (c) an ester compound having a halogen at the α position, thereby arriving at the present invention.

[0011] That is, the present invention is as follows.

[0012] 1. A composition for optical materials comprising (a) an episulfide compound, (b) a polymerization catalyst, and (c) an ester compound having a halogen at the α position.

[0013] 2. (a) A composition for optical materials described in 1, wherein the episulfide compound is a compound represented by the following formula (1).

[0014] [Chemical Formula 1]

[0015]

[0016] (where m is an integer from 0 to 4 and n is an integer from 0 to 2.)

[0017] 3. A composition for an optical material described in 1 or 2, further containing a polythiol compound.

[0018] 4. A composition for an optical material described in any one of 1 to 3, further containing sulfur and / or a compound represented by the following formula (9).

[0019] [Chemical Formula 2]

[0020]

[0021] (In the equation, X represents S, Se, or Te. a~f=0~3, 8≥(a+c+e)≥1, 8≥(b+d+f)≥2, and (b+d+f)≥(a+c+e).)

[0022] 5. An optical material composition described in any one of 1 to 4, wherein the ester compound having a halogen at the (c)α position is a compound represented by the following formula (10).

[0023] [Chemical Formula 3]

[0024]

[0025] (In the formula, X represents a halogen. R 1 and R 2 Each represents, independently, a hydrocarbon having 1 to 10 carbon atoms.

[0026] 6. A composition for an optical material described in 5, wherein the compound represented by the formula (10) above is one or more compounds selected from the group consisting of dimethyl chloromalonicate, diethyl chloromalonicate, dimethyl bromomalonicate, and diethyl bromomalonicate.

[0027] 7. An optical material obtained by polymerizing a composition for an optical material described in any one of 1 to 6 above. Effects of the invention

[0028] By the present invention, it has become possible to provide a composition for optical materials that suppresses the increase in viscosity during mixing, which was difficult in the prior art, and also maintains a good balance of the coloration of the resin after curing, the color change after heating the resin, and the color change after light irradiation of the resin. Specific details for implementing the invention

[0029] Hereinafter, the present invention will be described in detail by exemplifying manufacturing examples and embodiments. However, the present invention is not limited to the exemplified manufacturing examples and embodiments, and may be carried out by making any modifications as long as they do not significantly deviate from the content of the present invention.

[0030] (a) The episulfide compounds used in the present invention encompass all episulfide compounds, but are specifically listed as compounds having a chain-like aliphatic skeleton, an aliphatic cyclic skeleton, or an aromatic skeleton.

[0031] Examples of compounds having a chain-like aliphatic skeleton include compounds represented by the following formulas (1) to (4).

[0032] [Chemical Formula 4]

[0033]

[0034] (1) In the formula, m represents an integer from 0 to 4, and n represents an integer from 0 to 2. Preferably, n represents 0.

[0035] [Chemical Formula 5]

[0036]

[0037] [Chemical Formula 6]

[0038]

[0039] [Chemical Formula 7]

[0040]

[0041] Examples of compounds having an aliphatic cyclic skeleton include compounds represented by the following formula (5) or (6).

[0042] [Chemical Formula 8]

[0043]

[0044] (5) In the formula, p and q each independently represent integers from 0 to 4. Preferably, p represents 1 and q represents 2.

[0045] [Chemical Formula 9]

[0046]

[0047] (6) In the formula, p and q each independently represent integers from 0 to 4. Preferably, p represents 1 and q represents 2.

[0048] Examples of compounds having an aromatic backbone include compounds represented by the following formula (7) or (8).

[0049] [Chemical Formula 10]

[0050]

[0051] (7) In the formula, p represents an integer from 0 to 4 and q represents an integer from 1 to 3. Preferably, p represents 1 and q represents 2.

[0052] [Chemical Formula 11]

[0053]

[0054] (8) In the formula, p and q each independently represent an integer of 0 or 1. Preferably, p represents 1 and q represents 1.

[0055] Although specific examples have been shown above, the compounds (a) of the present invention are not limited to these, and these compounds (a) may be used alone or in combination of two or more types.

[0056] Among these, a preferred compound is a compound represented by formulas (1) and (2) having a chain-like aliphatic skeleton, specifically bis(β-epithiopropyl)sulfide, bis(β-epithiopropyl)disulfide, bis(β-epithiopropyl)trisulfide, bis(β-epithiopropylthio)methane, 1,2-bis(β-epithiopropylthio)ethane, 1,3-bis(β-epithiopropylthio)propane, 1,4-bis(β-epithiopropylthio)butane, bis(β-epithiopropylthioethyl)sulfide, and a compound of formula (2). Particularly preferred compounds are bis(β-epithiopropyl)sulfide (n=0 in formula (1) above), bis(β-epithiopropyl)disulfide (m=0, n=1 in formula (1) above), and the compound of formula (2), and the most preferred compound is bis(β-epithiopropyl)sulfide (n=0 in formula (1) above).

[0057] (b) As a polymerization catalyst for polymerizing and curing the composition used in the present invention, amines, onium salts, or phosphine compounds are used. Specific examples include amines, quaternary ammonium salts, quaternary phosphonium salts, tertiary sulfonium salts, secondary iodonium salts, and phosphine compounds. Among these, quaternary ammonium salts, quaternary phosphonium salts, and phosphine compounds that have good compatibility with the composition are more preferred, and even more preferably, quaternary phosphonium salts. Specific examples of more preferred compounds include quaternary ammonium salts such as tetra-n-butylammonium bromide, tetraphenylammonium bromide, triethylbenzylammonium chloride, cetyldimethylbenzylammonium chloride, and 1-n-dodecylpyridinium chloride; quaternary phosphonium salts such as tetra-n-butylphosphonium bromide and tetraphenylphosphonium bromide; and phosphine compounds such as triphenylphosphine. Among these, the more preferred compounds are triethylbenzylammonium chloride and tetra-n-butylphosphonium bromide, and the most preferred compound is triethylbenzylammonium chloride. The polymerization catalyst may be used alone or in a mixture of two or more types.

[0058] (b) The amount of polymerization catalyst added cannot be determined uniformly as it varies depending on the composition, mixing ratio, and polymerization curing method, but is typically used in an amount of 0.001 mass% or more and 5 mass% or less, preferably 0.01 mass% or more and 1 mass% or less, and most preferably 0.01 mass% or more and 0.5 mass% or less with respect to the total amount of the composition for optical materials. If the amount of polymerization catalyst added is greater than 5 mass%, the refractive index and heat resistance of the cured product may decrease, and discoloration may occur. Also, if it is less than 0.001 mass%, it may not be sufficiently cured and the heat resistance may be insufficient.

[0059] The ester compound having a halogen at the (c)α position used in the present invention comprises an ester compound having a halogen at all α positions, and is preferably a compound represented by the following formula (10).

[0060] [Chemical Formula 12]

[0061]

[0062] (10) In the formula, X represents a halogen, preferably Cl, Br, or I. R 1 and R 2 Each independently represents a hydrocarbon having 1 to 10 carbon atoms, preferably a hydrocarbon having 1 to 4 carbon atoms, and more preferably methyl, ethyl, or propyl.

[0063] Specifically, it is a halogenated malonic acid ester, more preferably a diester compound having a halogen at the α position, specifically dimethyl chloromalonicate, diethyl chloromalonicate, dimethyl bromomalonicate, and diethyl bromomalonicate. Among these, preferably dimethyl chloromalonicate and diethyl chloromalonicate.

[0064] (c) The amount of compound added is typically 0.0001 to 5.0 mass% with respect to the total amount of the composition for optical materials, preferably 0.0005 to 3.0 mass%, and more preferably 0.001 to 2.0 mass%. (c) If the amount of compound added is greater than 5.0 mass%, it may not be sufficiently cured, and the refractive index and heat resistance of the cured product may decrease, and if it is less than 0.0001 mass%, the viscosity may increase during mixing.

[0065] Meanwhile, a polythiol compound may be added to the composition for optical materials of the present invention. Polythiol compounds include all polythiol compounds, specifically methanedithiol, 1,2-dimercaptoethane, 2,2-dimercaptopropane, 1,3-dimercaptopropane, 1,2,3-trimercaptopropane, 1,4-dimercaptobutane, 1,6-dimercaptohexane, bis(2-mercaptoethyl)sulfide, 1,2-bis(2-mercaptoethylthio)ethane, 1,5-dimercapto-3-oxapentane, 1,8-dimercapto-3,6-dioxaoctane, 2,2-dimethylpropane-1,3-dithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-mercaptomethyl-1,3-dimercaptopropane, 2-mercaptomethyl1,4-dimercaptopropane, 2-(2-mercaptoethylthio)-1,3-dimercaptopropane, 1,2-bis(2-mercaptoethylthio)-3-mercaptopropane, 1,1,1-tris(mercaptomethyl)propane, tetrakis(mercaptomethyl)methane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), 1,4-Butanediolbis(2-mercaptoacetate), 1,4-Butanediolbis(3-mercaptopropionate), trimethylolpropanetris(2-mercaptoacetate), trimethylolpropanetris(3-mercaptopropionate), pentaerythritoltetrakis(2-mercaptoacetate), pentaerythritoltetrakis(3-mercaptopropionate), 1,1-Dimercaptocyclohexane, 1,2-Dimercaptocyclohexane, 1,3-Dimercaptocyclohexane, 1,4-Dimercaptocyclohexane, 1,3-Bis(mercaptomethyl)cyclohexane, 1,4-Bis(mercaptomethyl)cyclohexane, 2,5-Bis(mercaptomethyl)-1,4-Dithian, 2,5-Bis(mercaptoethyl)-1,4-dithian, 1,2-Bis(mercaptomethyl)benzene, 1,3-Bis(mercaptomethyl)benzene, 1,4-Bis(mercaptomethyl)benzene,Examples include bis(4-mercaptophenyl)sulfide, bis(4-mercaptophenyl)ether, 2,2-bis(4-mercaptophenyl)propane, bis(4-mercaptomethylphenyl)sulfide, bis(4-mercaptomethylphenyl)ether, 2,2-bis(4-mercaptomethylphenyl)propane, etc.

[0066] Although specific examples have been shown above, they are not limited to these, and these compounds may be used individually or in combination of two or more.

[0067] Specific examples of preferred compounds among the above include bis(2-mercaptoethyl)sulfide, pentaerythritoltetrakis(2-mercaptoacetate), pentaerythritoltetrakis(3-mercaptopropionate), 2,5-bis(mercaptomethyl)-1,4-dithian, 1,2-bis(2-mercaptoethylthio)-3-mercaptopropane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, and 1,3-bis(mercaptomethyl)benzene. Examples include 1,4-bis(mercaptomethyl)benzene. Specific examples of more preferred compounds are bis(2-mercaptoethyl)sulfide and 1,3-bis(mercaptomethyl)benzene, and the most preferred compound is bis(2-mercaptoethyl)sulfide.

[0068] The amount of polythiol compound added is preferably 1 to 50 mass% with respect to the total amount of the composition for optical materials, more preferably 2 to 30 mass%, and even more preferably 3 to 20 mass%.

[0069] Meanwhile, sulfur or a compound represented by (9) may be added to the composition for optical materials of the present invention.

[0070] [Chemical Formula 13]

[0071]

[0072] (9) In the formula, X represents S, Se or Te, preferably S. a to f each independently represent integers from 0 to 3, and 8≥(a+c+e)≥1, 8≥(b+d+f)≥2, and (b+d+f)≥(a+c+e).

[0073] (9) Compounds represented by the formula include all compounds, specifically dithiran, 1,2-dithiethane, 1,3-dithiethane, trithiethane, 1,2-dithiolan, 1,3-dithiolan, 1,2,3-trithiolan, 1,2,4-trithiolan, tetrathiolan, 1,2-dithian, 1,3-dithian, 1,4-dithian, 1,2,3-trithian, 1,2,4-trithian, 1,3,5-trithian, 1,2,3,4-tetrathian, 1,2,4,5-tetrathian, bis(1,2,3,5,6-pentathiephano)methane, tris(1,2,3,5,6-pentathiephano)methane, 1,2-dithiephan, 1,3-Ditiephan, 1,4-Ditiephan, 1,2,3-Tritiephan, 1,2,4-Tritiephan, 1,2,5-Tritiephan, 1,3,5-Tritiephan, 1,2,3,4-Tetrathiephan, 1,2,3,5-Tetrathiephan, 1,2,4,5-Tetrathiephan, 1,2,4,6-Tetrathiephan, 1,2,3,4,5-Pentathiephan, 1,2,3,4,6-Pentathiephan, 1,2,3,5,6-Pentathiephan, Hexathiephan, Disereccyclobutane, Tricereccyclobutane, Disereccyclopentane, Tricereccyclopentane, Tetracereccyclopentane, Disereccyclohexane, Examples include tricerecyclohexane, tetracerecyclohexane, pentacerecyclohexane, dicerecycloheptane, tricerecycloheptane, tetracerecycloheptane, pentacerecycloheptane, hexacerecycloheptane, ditellurocyclobutane, tritellurocyclobutane, ditellurocyclopentane, tritellurocyclopentane, tetratellurocyclopentane, ditellurocyclohexane, tritellurocyclohexane, tetratellurocyclohexane, pentatellurocyclohexane, ditellurocycloheptane, tritellurocycloheptane, tetratellurocycloheptane, pentatellurocycloheptane, and hexatellurocycloheptane.

[0074] Specific examples of the preferred type include 1,2-dithiethane, trithiethane, 1,2-dithiolan, 1,2,3-trithiolan, 1,2,4-trithiolan, tetrathiolan, 1,2-dithiane, 1,2,3-trithiane, 1,2,4-trithiane, 1,3,5-trithiane, 1,2,3,4-tetrathiane, 1,2,4,5-tetrathiane, pentathian, 1,2,3-trithiepane, 1,2,4-trithiepane, 1,2,5-trithiepane, 1,2,3,4-tetrathiepane, 1,2,3,5-tetrathiepane, 1,2,4,5-tetrathiepane, 1,2,4,6-tetrathiepane, 1,2,3,4,5-pentathieepane, 1,2,3,4,6-pentatiepan, 1,2,3,5,6-pentatiepan, and hexatiepan, and particularly preferably 1,2,3,5,6-pentatiepan.

[0075] When using sulfur or a compound represented by formula (9), it is preferable to react it with compound (a) in advance. The conditions for this preliminary polymerization reaction are preferably 0.1 to 240 hours at -10°C to 120°C, more preferably 0.1 to 120 hours at 0°C to 100°C, and particularly preferably 0.1 to 60 hours at 20°C to 80°C. Using a catalyst to carry out a preliminary reaction is effective, and preferred examples include 2-mercapto-1-methylimidazole, triphenylphosphine, 3,5-dimethylpyrazole, N-cyclohexyl-2-benzothiazolylsulfinamide, dipentamethylenethiuram tetrasulfide, tetrabutylthiuram disulfide, tetraethylthiuram disulfide, 1,2,3-triphenylguanidine, 1,3-diphenylguanidine, 1,1,3,3-tetramethyleneguanidine, aminoguanidineurea, trimethylthiourea, tetraethylthiourea, dimethylethylthiourea, zinc dibutyldithiocarbamate, zinc dibenzyldithiocarbamate, zinc diethyldithiocarbamate, zinc dimethyldithiocarbamate. Examples include pipecollium pipecholyl dithiocarbamate. Furthermore, it is preferable to consume at least 10% (pre-reaction value is 100%) of sulfur or a compound represented by formula (9) through this preliminary polymerization reaction, and it is more preferable to consume at least 20%. The preliminary reaction can be carried out under any atmosphere, such as under an inert gas such as air or nitrogen, under atmospheric pressure or under a sealed environment with increased or decreased pressure. Meanwhile, it is also possible to use liquid chromatography or a refractive index meter to detect the progress of the preliminary reaction.

[0076] The amount of sulfur or the compound represented by (9) added is typically 0.01 to 40 mass% with respect to the total amount of the optical material composition, preferably 0.1 to 30 mass%, and more preferably 0.5 to 25 mass%.

[0077] In the present invention, it is preferable to perform a degassing treatment on the composition for optical materials in advance. The degassing treatment is performed under reduced pressure before, during, or after mixing a compound capable of reacting with some or all of the compositional components, a polymerization catalyst, and an additive. Preferably, it is performed under reduced pressure during or after mixing. The treatment conditions are performed under reduced pressure of 0.001 to 50 torr, for 1 minute to 24 hours, and at 0°C to 100°C. The degree of reduced pressure is preferably 0.005 to 25 torr, more preferably 0.01 to 10 torr, and the degree of reduced pressure may be varied within these ranges. The degassing time is preferably 5 minutes to 18 hours, and more preferably 10 minutes to 12 hours. The temperature during degassing is preferably 5°C to 80°C, more preferably 10°C to 60°C, and the temperature may be varied within these ranges. During degassing treatment, renewing the interface of the optical material composition by means of stirring, blowing gas, or vibration by ultrasound is a desirable operation for enhancing the degassing effect. The components removed by degassing treatment are mainly dissolved gases such as hydrogen sulfide or low-boiling point substances such as low molecular weight thiols, but the type of components to be removed is not particularly limited as long as the effect of the present invention is exhibited.

[0078] Furthermore, it is desirable to purify each raw material before mixing and the composition for these optical materials by filtering out impurities, etc., using a filter having a hole diameter of about 0.05 to 10 μm, in order to further improve the quality of the optical materials of the present invention.

[0079] In addition, when obtaining an optical material by polymerizing and curing the composition for optical materials of the present invention, it is of course possible to further improve the practicality of the obtained material by adding known additives such as antioxidants, UV absorbers, and bluening agents.

[0080] Preferred examples of antioxidants include phenol derivatives. Among these, preferred compounds are polyphenols and halogen-substituted phenols, more preferred compounds are catechol, pyrogallol, and alkyl-substituted catechols, and most preferred compounds are catechol and pyrogallol. Preferred examples of UV inhibitors include benzotriazole compounds. Among these, specific examples of preferred compounds are 2-(2-hydroxy-5-methylphenyl)-2H-benzotriazole, 5-chloro-2-(3,5-di-tert-butyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chloro-2H-benzotriazole, 2-(3,5-di-tert-pentyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-4-octyloxyphenyl)-2H-benzotriazole, and 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole. Desirable examples of bluing agents include anthraquinone compounds.

[0081] In addition, if the composition for optical materials of the present invention is prone to peeling off from the mold during polymerization, it is also possible to control and improve the adhesion between the obtained cured product and the mold by using or adding a known external and / or internal adhesion improving agent. Examples of adhesion improving agents include known silane coupling agents or titanate compounds, and these may be used individually or in a mixture of two or more types. The amount added is typically 0.0001 to 5 mass% with respect to the total amount of the composition for optical materials. Conversely, if the composition for optical materials of the present invention is difficult to peel off from the mold after polymerization, it is also possible to improve the release properties of the obtained cured product from the mold by using or adding a known external and / or internal release agent. Examples of release agents include fluorine-based nonionic surfactants, silicone-based nonionic surfactants, phosphate esters, acidic phosphate esters, oxyalkylene-type acidic phosphate esters, alkali metal salts of acidic phosphate esters, alkali metal salts of oxyalkylene-type acidic phosphate esters, alkali metal salts of higher fatty acids, higher fatty acid esters, paraffin, wax, higher aliphatic amides, higher aliphatic alcohols, polysiloxanes, aliphatic amine ethylene oxide adducts, etc., and these may be used individually or in a mixture of two or more types. The amount added is typically 0.0001 to 5 mass% with respect to the optical material composition.

[0082] The method for manufacturing an optical material by polymerizing and curing the composition for optical materials according to the present invention is described in more detail as follows. The aforementioned compositional components, additives such as antioxidants, UV absorbers, polymerization catalysts, radical polymerization initiators, adhesion improvers, and release agents may all be mixed simultaneously under stirring within the same container, or the raw materials may be added and mixed in stages, or the various components may be mixed separately and then remixed within the same container. The order in which the raw materials and auxiliary materials are mixed does not matter. In the mixing process, the set temperature and the time required are basically sufficient conditions for each component to be sufficiently mixed.

[0083] The composition for optical materials, having undergone the reaction and treatment described above, is injected into a mold made of glass or metal, and after a polymerization-curing reaction proceeds by heating or irradiation with active energy rays such as ultraviolet rays, it is separated from the mold. In this way, an optical material is manufactured. The composition for optical materials is preferably polymerized and cured by heating, and an optical material is manufactured. In this case, the curing time is 0.1 to 200 hours, typically 1 to 100 hours, and the curing temperature is -10 to 160°C, typically -10 to 140°C. Polymerization can be performed by holding at a predetermined polymerization temperature for a predetermined time, increasing the temperature by 0.1°C to 100°C / hour, decreasing the temperature by 0.1°C to 100°C / hour, and combinations thereof. Furthermore, in the method for manufacturing an optical material according to the present invention, performing an annealing treatment on the cured material at a temperature of 50 to 150°C for about 10 minutes to 5 hours after the polymerization is completed is a preferred treatment to remove deformation of the optical material. Additionally, surface treatments such as dyeing, hard coating, impact-resistant coating, anti-reflective properties, and anti-fog properties may be performed as needed.

[0084] The composition for optical materials of the present invention preferably has a viscosity of less than 450 cp, measured by a vibratory viscometer, after uniformly stirring each component and maintaining it at 20°C for 3 hours, and more preferably less than 350 cp.

[0085] Furthermore, when the composition for optical materials of the present invention is polymerized and cured and a 48-hour weathering test is performed to measure the change in color tone, it is preferable that ΔY.I. is less than 3.5, and more preferable that it is less than 2.5.

[0086] Examples

[0087] The present invention will be specifically described below by way of examples, but the present invention is not limited thereto. Meanwhile, the evaluation was performed by the following method.

[0088] To the compounds shown in Tables 3 and 4 below ((a) compounds, sulfur, and polythiol compounds), 0.03 mass% of triethylbenzylammonium chloride as (b) polymerization catalyst and 0.3 mass% of the stabilizer shown in Tables 3 and 4 were added relative to the total amount of the optical material composition. After uniform stirring, the mixture was maintained at 20°C for 3 hours, and viscosity was measured using a vibratory viscometer (Seconic VM-10A). Specifically, approximately 30 mL of the solution was taken into a 100 mL plastic container, left to stand in a furnace at 20°C, and the viscosity was measured. The results based on the evaluation criteria shown in Table 1 below are shown in Tables 3 and 4.

[0089] [Table 1]

[0090]

[0091] To the compounds shown in Tables 3 and 4 below ((a) compounds, sulfur, and polythiol compounds), 0.03 mass% of triethylbenzylammonium chloride as (b) polymerization catalyst and 0.3 mass% of the stabilizer shown in Tables 3 and 4 were added to the total amount of the optical material composition, and polymerization curing was performed. A weathering test device (Atlus weathermeter Ci4000) was used, and a 48-hour weathering test was conducted under conditions of a black panel temperature of 60°C and a humidity of 50%. The change in color tone (yellowness (ΔY.I.)) before and after the weathering test was measured using a Konica Minolta spectrophotometer CM-5. Specifically, the YI of a sample (t=5mm) was measured in advance under conditions of 25℃, and the above weathering test was performed on this sample. After leaving it in a room at 25℃ for at least 30 minutes, the YI was measured again. The difference in YI before and after the weathering test was denoted as ΔY.I. The results based on the evaluation criteria shown in Table 2 below are shown in Tables 3 and 4.

[0092] [Table 2]

[0093]

[0094] [Table 3]

[0095]

[0096] Compound abbreviation

[0097] BES: Bis(β-epithiopropyl)sulfide

[0098] S: Yellow

[0099] BMES: Bis(2-mercaptoethyl)sulfide

[0100] [Table 4]

[0101]

[0102] Compound abbreviation

[0103] BES: Bis(β-epithiopropyl)sulfide

[0104] S: Yellow

[0105] BMES: Bis(2-mercaptoethyl)sulfide

Claims

Claim 1 A composition for an optical material comprising (a) an episulfide compound, (b) a polymerization catalyst, and (c) an ester compound having a halogen at the α position, wherein the ester compound having a halogen at the α position is a compound represented by the following formula (10). (In the formula, X represents a halogen. R 1 and R 2 Each represents, independently, a hydrocarbon having 1 to 10 carbon atoms. Claim 2 A composition for optical materials according to claim 1, wherein the (a) episulfide compound is a compound represented by the following formula (1). (where m is an integer from 0 to 4 and n is an integer from 0 to 2.) Claim 3 A composition for optical materials according to claim 1, further containing a polythiol compound. Claim 4 A composition for optical materials according to claim 1, further containing sulfur and / or a compound represented by the following formula (9). (In the equation, X represents S, Se, or Te. a~f=0~3, 8≥(a+c+e)≥1, 8≥(b+d+f)≥2, and (b+d+f)≥(a+c+e).) Claim 5 delete Claim 6 A composition for optical materials according to claim 1, wherein the compound represented by the formula (10) above is one or more compounds selected from the group consisting of dimethyl chloromalonicate, diethyl chloromalonicate, dimethyl bromomalonicate, and diethyl bromomalonicate. Claim 7 An optical material obtained by polymerizing a composition for optical materials described in any one of claims 1 to 4 and 6.

Citation Information

Patent Citations

  • Composition for resin

    JP2013100534A

  • Composition for optical materials

    WO2013133144A1

  • Composition for optical material and optical material

    JP2017114972A

  • Curable composition

    KR1020080007562A